TAXONOMY AND MORPHOLOGY OF SPECIES OF THE GENUS HIPPODAMIA (CHEVROLAT IN DEJEAN, 1837), COMMON IN THE KASHKADARYA REGION (Scientific journal of the Fergana State University, 2025)
The article presents the taxonomy, morphology, and coordinates of species of the genus Hippodamia (Chevrolat in Dejean, 1837), common in the Kashkadarya region. As a result of practical research, the systematics, species composition, morphology, and global distribution of species of the genus Hippodamia (Chevrolat in Dejean, 1837), common in the mountainous, hilly, and cultivated desert areas of the Kashkadarya region, were studied. During the study and identification of the collected specimens, the following species were identified and recorded for the region: H. variegata (Goeze, 1777), H. tredecimpunctata (Linnaeus, 1758), H. heydeni (Weise, 1892). The occurrence of the identified species in all vertical zones indicates their ecological plasticity.